Novel Insights into the Effect of Pythium Strains on Rapeseed Metabolism - Bělonožníková, Kateřina; Vaverová, Kateřina; Vaněk, Tomáš; Kolařík, Miroslav; Hýsková, Veronika; Vaňková, Radomíra; Dobrev, Petre; Křížek, Tomáš; Hodek, Ondřej; Čokrtová, Kateřina; Štípek, Adam; Ryšlavá, Helena (Microorganisms, 2020)
Pythium oligandrum is a unique biological control agent. This soil oomycete not only acts as a mycoparasite, but also interacts with plant roots and stimulates plant defense response via specific elicitors. In addition, P. oligandrum can synthetize auxin precursors and stimulate plant growth. We analyzed the secretomes and biochemical properties of eleven Pythium isolates to find a novel and effective strain with advantageous features for plants. Our results showed that even closely related P. oligandrum isolates significantly differ in the content of compounds secreted into the medium, and that all strains secrete proteins, amino acids, tryptamine, phenolics, and hydrolytic enzymes capable of degrading cell walls (endo-β-1,3-glucanase, chitinase, and cellulase), exoglycosidases (especially β-glucosidase), proteases, and phosphatases. The most different strain was identified as a not yet described Pythium species. The changes in metabolism of Brassica napus plants grown from seeds coated with the tested Pythium spp. were characterized. Enhanced levels of jasmonates, ethylene precursor, and salicylic acid may indicate better resistance to a wide variety of pathogens. Glucosinolates, as defense compounds against insects and herbivores, were enhanced in young plants. Altogether, P. oligandrum strains varied in their life strategies, and either they could perform equally as plant growth promoters and mycoparasites or they had developed one of these strategies better.
Keywords: cultivation medium; rapeseed; Pythium; phytohormones; plant metabolism; enzyme activities; secretome